Energy analysis and value evaluation of water use process in different land types based on the water-carbon cycle - Xi Guo; Mengzhu Cui; Cuimei Lv; Mengmeng Jiang; Denghua Yan (Ecological Indicators)
The scientific identification and evaluation of the ecological and economic value of water and land resources is fundamental for the rational allocation and sustainable utilization. However, traditional research often approaches this issue from an economic perspective, uses value-equivalent method for quantitative analysis, and fails to delve into the internal energy flows and values within the ecological and economic system. Therefore, this study undertook an innovative approach by examining the water use process under the water-carbon cycle across various land types, identified the diverse values generated within this process, and realized uniform measurement based on the emergy. This research focused on Luoyang City as the study area, and provided a detailed quantitative analysis of the city’s ecological and values from 2017 to 2021. The results indicated that the overall value of water and land resources in Luoyang City showed a downward trend, with the values of different subsystems ranked in descending order as follows: building land > forest and grassland > water > cropland. This study offers a cohesive quantitative analysis method for the rational development and comprehensive utilization of regional water and land resources.